주택가격채널: 거시경제에 미치는 영향을 중심으로 - 송인호 (13866, 2014)
This paper investigates the manner in which house prices affect macroeconomic variables through a house price channel by applying the method of Iacoviello (2005) to Korean data, and establishing a DSGE model with complementarity. This paper found that hig